News Framing Analysis about Sexual Harassment on Men in the Work Environment KPI on Online Media (detik.com and tribunnews.com) - Tri Melisa Selviani; Sunarto Sunarto (Budapest International Research and Critics University, 2022)
The pervasive nature of sexual harassment makes it a complex, elusive, and hard to prove crime. News of this kind of case can be found on some media platforms with various speculations that do not necessarily support the victim. These 'leanings' are often found in online news. The main focus of this research is the framing of online media regarding the case of an employee of the Indonesian Broadcasting Commission (KPI) who was a victim of sexual harassment by colleagues. This study uses a descriptive qualitative method with a critical paradigm using the Robert M. Entman model frame analysis to answer the research question with the object of the study being the news from detik.com and tribunnews.com related to the sexual harassment case. The result of the analysis reveals that the reporting from detik.com and tribunnews.com provides their own biased descriptions. These media representations did not only cover the side of the victim but also that of the institution.